2021
DOI: 10.1177/08944393211005468
|View full text |Cite
|
Sign up to set email alerts
|

Selective Avoidance on Social Media: A Comparative Study of Western Democracies

Abstract: This study examines the phenomena of political unfriending and content removal on social media in three Western democracies—France, the United Kingdom, and the United States. We seek to understand the role of crosscutting discussion, confrontational discussion style, and ideological extremity in triggering unfriending and content removal on social media, while shedding light on cross-country differences. The findings show that selective avoidance behaviors are much more common in the United States than either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
0
8
0
2
Order By: Relevance
“…At least two prior studies have found evidence of a connection between discussion network size and politically motivated unfriending (Skoric et al, 2018; Zhu & Skoric, 2021; but see Zhu et al, 2017). One potential explanation for this connection is the prevalence of political disagreement in diverse networks (Peacock, 2021; Skoric et al, 2021). Although diversity and disagreement are distinct phenomena, they are closely related and share some operational overlap (Barnidge, 2017).…”
Section: Egocentric Publicsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least two prior studies have found evidence of a connection between discussion network size and politically motivated unfriending (Skoric et al, 2018; Zhu & Skoric, 2021; but see Zhu et al, 2017). One potential explanation for this connection is the prevalence of political disagreement in diverse networks (Peacock, 2021; Skoric et al, 2021). Although diversity and disagreement are distinct phenomena, they are closely related and share some operational overlap (Barnidge, 2017).…”
Section: Egocentric Publicsmentioning
confidence: 99%
“…To this point, most scholarship has focused on predictors of selective avoidance including individuals’ motivations, preferences, and other psychological factors (John & Dvir-Gvirsman, 2015; John & Gal, 2018; Neubaum et al, 2021), as well as outcomes such as political participation and expression (e.g., Kim et al, 2021; Zhu et al, 2017). While some research has examined individuals’ social media networks as predictors (John & Dvir-Gvirsman, 2015; Yang et al, 2017; Zhu et al, 2017; Zhu & Skoric, 2021), and other work has examined the antecedent role of cross-cutting discussion or discussion with weak ties (Skoric et al, 2018, 2021; Yang et al, 2017), most prior studies do not place central focus on the role of social or discussion network structures, and the work that has been done has examined only one or two aspects of social media networks. Thus, there is a need in the literature to establish a systematic set of results from a broad-base of evidence about the relationships between network characteristics and selective avoidance.…”
mentioning
confidence: 99%
“…En principio, estas acciones no deberían considerarse como problemáticas ni patológicas, puesto que se están convirtiendo en prácticas cada vez más frecuentes a la hora de combatir las amenazas (reales o percibidas) procedentes de la hiperconectividad digital (Kaun 2021). La literatura existente sobre ese tema se ha centrado tanto en el filtrado de contenido (es decir, bloquear, silenciar o dejar de seguir a un perfil) como en la exclusión social (eliminar amistades), a la vez que ha investigado la manera en que las personas comparten con otras sus estrategias a la hora de evitar el contacto social (Skoric et al 2021; John y Agbarya 2020; Skoric, Zhu y Lin 2018; Bode 2016; John y Dvir-Gvirsman 2015). En este estudio, nos centramos principalmente en el hecho de eliminar una amistad como la estrategia más severa a la hora de evitar el contacto social, que también tiene consecuencias directas en la conectividad social de los individuos.…”
Section: Evitación Y Desconexión: Creando Espacios Digitales Segurosunclassified
“…Dicho esto, cabe destacar que, mientras que la gente considera un tercio de sus amistades en Facebook como potenciales candidatas a ser eliminadas, muchas veces se abstienen de hacerlo, dado que no quieren perder la posibilidad de estar en contacto con ellas, en el caso de que fuera necesario (Krämer, Hoffmann y Eimler 2015). De hecho, muchos estudios han demostrado que la gran mayoría de los ciudadanos no elimina amistades por razones políticas, y el número de aquellos que han declarado hacerlo oscila entre el 10 y el 30 por ciento (Skoric et al 2021;Skoric, Zhu y Lin 2018;John y Dvir-Gvirsman 2015). Los estudios llevados a cabo en este ámbito han demostrado también que los ciudadanos desarrollan otras formas de evitación (más moderadas) en las PRS, los llamados "comportamientos de teflón", que incluyen abstenerse completamente del comentar o empezar una discusión política, a la vez que siguen conectados con sus contactos en las redes sociales (Goyanes y Skoric 2021).…”
Section: Conclusiones Y Futuras Líneas De Investigaciónunclassified
“…Such diminishing levels of exposure to attitude-challenging political information have raised concerns about homogeneous opinion networks, sometimes referred to as “echo chambers” (Vraga & Tully, 2021; Zuiderveen Borgesius et al, 2016). They are characterized by selective exposure which describes the selection of information that is consistent with our attitudes, and selective avoidance, that is, the avoidance of information that challenges our attitudes (Skoric et al, 2021; Zhu et al, 2017). As a consequence, homogeneous opinion networks could put a threat to the quality of democracy, as they may foster polarization and impair the heterogeneity of the public political discourse.…”
mentioning
confidence: 99%